DETERMINATION OF FATTY ACIDS IN SOLANUM SURATTENSE BURM. F. BY USING GAS CHROMATOGRAPHY - Preet, Raman; Gupta, Raghbir Chand (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study aims to document the fatty acid composition of Solanum surattense Burm. f. collected from hot desert of India, Rajasthan. Methods: The fatty acid analysis was performed by gas chromatography-flame ionization detector (GC-FID). The operating conditions used to examine methyl esters of fatty acids are as follows. Fatty acids were converted into methyl esters (FAMEs) before GC analysis according to the standard methods by Ranganna (1986). Quantitative determinations of FAMEs were conducted using GC-FID and capillary column HP-88 Agilent Technologies. Results: The most abundant fatty was palmitic acid (13.2%), oleic acid (22.9%), and linoleic acid (11.9%). This plant is good source of important fatty acids including all the groups of saturated, monounsaturated, and polyunsaturated fatty acids (MUFAs and PUFAs) and can be used as a commercial source of fatty acids especially MUFAs and PUFAs. Conclusion: The plant is well studied for various pharmacological activities such as antiasthmatic, anticancer, cardiovascular, and hepatoprotective. Determination of fatty acid profiles in nutritional and clinical research with precision and fastness has become popular for human health and basic research.